IMPLEMENTATION OF TEACHER PERFORMANCE ASSESSMENT PROGRAM - Buyamin, Buyamin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Teacher Performance Assessment applied by the Head of the madrasah can provide practical encouragement for teachers to find out the advantages and disadvantages of each teacher in carrying out coaching for teachers so that they can focus more on improving learning in madrasahs by using a self-reflection approach as a renewal in Teacher Performance Assessment. This study aims to report on the program, implementation, effectiveness, constraints and follow-up of Teacher Performance Assessment by the Head of the madrasah. This research is qualitative with a case study method, presented in a descriptive-analytical manner. Data collection with Observation, Questionnaires, interviews, FGD (Focus Group Discussion), and document studies. The data sources consist of Madrasah Supervisors, Madrasah Heads, Deputy Heads of Curriculum, and subject teachers in one Tsanawiyah Madrasah in the Probolinggo Regency, East Java. Teknik analisis data melalui reduksi data, penyajian data, penarikan kesimpulan. Uji keabsahan datanya dengan triangulasi. The results showed that 1) the implementation of the Teacher Performance Assessment program includes goal setting, curriculum application and development, evaluation of learning tools, teaching methods, learning activities, and development of student learning experiences; 2) Performance Appraisal is carried out by pre-observation, observation, and post-observation, 3) the implementation of Teacher Performance Assessment in madrasahs is quite adequate 4) there are obstacles in its implementation, namely internal and external constraints, 5) follow-up of Teacher Performance Assessment by Conducting PKB-Guru (Sustainable Performance Assessment). This research contributes to inspiring teachers to update activities using a self-reflection approach.